The resilience engineering view on the work of control rooms operator of an energy distribution company - Wachs, Priscila (2019)
The variability and complexity of work in the electricity distribution assigns to teams involved (operators and electricians, for example) the development of resilience skills (RS). Resilience engineering is presented as a paradigm for safety management of complex systems, which aims to measure, evaluate and improve system´s resilience. The present study aimed to identify operator´s RS, factors to include in training scenarios, recommendations for re-designing the socio-technical system, and characteristics of interaction between operator and electrician. Interviews, field observation and document analysis were the instruments used to collect data. 15 resilience skill´s categories, 12 categories of factors for training scenarios and 16 recommendations for re-designing the system were identified. The analysis of the operator-electrician interaction disclosed 11 operator´s HR related to electricians, nine training factors for operators related to electricians and five factors for electricians related to operators. This result reinforces the importance of developing training scenarios that integrate operator and electrician tasks.